Experimenting with Ethnography A Companion to Analysis - Ballestero, Andrea; Winthereik, Brit Ross (Duke University Press, 2021)
An indispensable guide for all ethnographers, Experimenting with Ethnography collects twenty-one essays that offer concrete suggestions for thinking about and doing ethnographic research and writing.